The Examples of Personal and Household Financial Planning and Management in Improving Prosperity - Tarigan, Lukas (Universitas Kristen Indonesia, 2017)
We often do not plan and manage the use of personal funds households funds. As a result of this, many people complain about finances. This study is a type of literature research study, by looking for reference theory relevant to the problem found. The type of data used by the author is primary data through observation and secondary data. Actually, although our income is small, if we planned and managed well, then it will result in a better level of welfare. Keywords: Financial Planning, Personal Management, Prosperity